Interspeech 2015 2015
DOI: 10.21437/interspeech.2015-466
|View full text |Cite
|
Sign up to set email alerts
|

Classifiers for synthetic speech detection: a comparison

Abstract: Automatic speaker verification (ASV) systems are highly vulnerable against spoofing attacks, also known as imposture. With recent developments in speech synthesis and voice conversion technology, it has become important to detect synthesized or voice-converted speech for the security of ASV systems. In this paper, we compare five different classifiers used in speaker recognition to detect synthetic speech. Experimental results conducted on the ASVspoof 2015 dataset show that support vector machines with genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…However, recent studies have shown that a well-trained ASV system could be deceived by malicious attacks [1][2][3]. In the last decade, the speaker verification community held several ASVspoof challenge competitions [4][5][6] to develop countermeasures mainly against replay [7,8], speech synthesis [9,10] and voice conversion [10,11] attacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have shown that a well-trained ASV system could be deceived by malicious attacks [1][2][3]. In the last decade, the speaker verification community held several ASVspoof challenge competitions [4][5][6] to develop countermeasures mainly against replay [7,8], speech synthesis [9,10] and voice conversion [10,11] attacks.…”
Section: Introductionmentioning
confidence: 99%
“…A separate detection countermeasure has the following advantages: 1) It separates the defense part and speaker verification into two independent stages, which avoids retraining a well-developed ASV model. 2) Since most existing countermeasures for replay and synthetic speech attacks are based on a separate detection network [7][8][9], the proposed approach provides the feasibility to develop a unified countermeasure against all spoofing attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Gaussian Mixture Model (GMM) classifier trained with constant Q cepstral coefficient (CQCC) feature has been the benchmark for various anti-spoofing tasks [13,14]. The CQCC feature is a perceptually-inspired time-frequency analysis extracted from a constant-Q transform (CQT) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate the result using conventional MFCCs and newly proposed CQCCs features on GMM-maximum likelihood (GMM-ML) framework. It is found that GMM-ML as a classifier is better suited for spoofing detection task [19]. We have experimented on two recent databases: ASVspoof 2015, developed as a part of Automatic Speaker Verification Spoofing and Countermeasure Challenge [20] and BTAS 2016 corpus in Speaker Anti-spoofing Competition [21].…”
Section: Introductionmentioning
confidence: 99%